Into the deep : a memoir from the man who found Titanic - Ballard, Robert D.; Drew, Christopher, 1956- (National Geographic, 2021)
"Oceanographer and marine biologist Robert D. Ballard looks back on a long and storied life that includes accomplishments ranging from discovering new life-forms to finding the wreck of the Titanic"--